Exploratory Activities in Educational Games using Fuzzy Logic - Anggy Giri Prawiyogi; Riya Widayanti (Pandawan Sejahtera Indonesia, 2023)
In educational games, one of the concepts for designing activities is the use of gratitude. Learning consists of the discovery, dream, design, and destiny phases. exploration activity or discovery search and exploration are the main activities. search activity, exploration, it takes quite a long time and involves uncertainty in its execution. Reward we need momentum to continue this discovery effort. Good rewards Keep You Focused players search and explore by providing performance metrics. This study use fuzzy logic to shape dynamic rewards behavior in discovery activities. The standard the input used is the fraction of exploration and time to generate a dynamic reward discovery activity. As a result of this research, fuzzy logic can generate three levels of reward variants.